Flame time of a cigarette lighter to achieve temperature capable of inflicting a burn. Issue 6 (September 2017) - Harel, Svetlana; Burkey, Brooke; Nanassy, Autumn D.; Marcolongo, Michele; Phillips, Evan; Campbell, Christine; McColgan, Maria D.
Highlights: Cigarette lighters must heat for 50 s (upright) to inflict skin burns. Non-intentional cigarette lighter burns are unlikely. Intent and preparation are needed to inflict burns with a cigarette lighter. These findings are of potential interest for child-abuse and other forensic cases. Abstract: Objective: Cigarette lighters are frequent vectors in intentional contact burns. Time and temperature needed to cause thermal injury are considered to differentiate accidental from inflicted burns. This study examines the minimum time needed to heat a cigarette lighter's top to temperatures capable of inflicting any clinically visible skin burn. This information could be useful in child abuse and other forensic cases. Methods: A literature search was performed to establish the time and temperature at which partial/full thickness skin burns are acquired, regardless of vector. Using a thermocouple, the temperature of the top of two common lighters was measured at ten second intervals while sustaining maximal flame held both upright and sideways and during cooling once the flame was extinguished. Results: In the literature, the lowest temperatures documented to cause burns in one second were 69 °C–70 °C for transepidermal or partial thickness burns. From an ambient temperature prior to flame ignition, it took over 50 s for the lighter tops to reach 60 °C when held upright. After 180 s, the lighters were shut off. It then took less than 60 s for the lighters to cool to less than 60 °C. The BIC lighter held to the side heated to 60 °C in about 15 s and needed over 100 s to cool to under 60 °C. Conclusions: Cigarette lighter burns are often blamed on non-intentional occurrences. At least 50 s of sustained flame is needed to heat typical cigarette lighter tops to temperatures capable of inflicting clinically visible skin burns. This time is longer than the time required to light a cigarette. Therefore, for a cigarette lighter to inflict a contact burn injury, there needs to be intent and preparation, making accidental cigarette lighter burns unlikely.